Analysis of school strategic management policy in optimizing edupark to improve physical activity and environmental literacy - Aprilla, Indri Ribut; Khamidi, Amrozi; Purwoko, Budi; Hazin, Mufarrihul (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
21st century education demands the development of holistic skills of students that are not only focused on academic aspects, but also on strengthening character, physical health, and environmental awareness. This study aims to analyze the strategic management policy of schools in optimizing the function of Edupark as a means of increasing physical activity and environmental literacy of students.This study uses a qualitative approach with a case study design. The research sample in the planning, implementation, and evaluation of the Edupark policy in Junior High Schools in Surabaya City amounted to 25 samples consisting of five principals, ten physical education subject teachers. The results of the interview study, the majority of respondents agreed that Edupark plays an important role in supporting physical activities with an average of 4.1 and contributing to environmental literacy with an average of 3.7. The challenges faced are limited facilities and time, which are reflected in the average value of 3.9. The results of the use of edupark for physical and sports activities are 65%, learning about the environment is 55% and interdisciplinary learning is 35%. The results of teacher perceptions of edupark include an increase in student physical activity of 72%, an increase in environmental knowledge of 58%, students are more involved in environmental issues 55%. The conclusion is that clear and structured managerial policies play an important role in the success of the use of Edupark to support students' physical activities and environmental literacy. Suggestions for further research can integrate Edupark and the education curriculum, as well as the addition of facilities and resources to support learning activities.